Kim - Kipling, Rudyard, 1865-1936 (Salt Lake City, UT : Project Gutenberg, 2000)
"Kim" by Rudyard Kipling is a novel first published in 1901. It follows the adventures of an orphaned Irish boy living as a street vagabond in late 19th-century India. Kim befriends a Tibetan lama seeking spiritual enlightenment and becomes his disciple. Their journey along the Grand Trunk Road draws Kim into the dangerous world of British espionage and the Great Game$1 (Bthe covert struggle between Russia and Britain for control of Central Asia. The novel vividly portrays India's cultures, religions, and teeming populations. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Kim_(novel)
Release date is 2000-06-01
Keywords: Orphans -- Fiction; India -- Fiction; Boys -- Fiction; Adventure stories; Spy stories; Lamas -- Fiction; Irish -- India -- Fiction